Bidirectional modulation of synaptic transmission by insulin-like growth factor-I - Noriega-Prieto, José Antonio; Maglio, Laura Eva; Perez-Domper, Paloma; Dávila, José Carlos; Gutiérrez, Antonia; Torres-Alemán, Ignacio; Fernández de Sevilla, David (Frontiers in Cellular Neuroscience, 2024)
Insulin-like growth factor-I (IGF-I) plays a key role in the modulation of synaptic plasticity and is an essential factor in learning and memory processes. However, during aging, IGF-I levels are decreased, and the effect of this decrease in the induction of synaptic plasticity remains unknown. Here we show that the induction of N-methyl-D-aspartate Receptor (NMDAR)-dependent long-term potentiation (LTP) at layer 2/3 pyramidal neurons (PNs) of the mouse barrel cortex is favored or prevented by IGF-I (10nM) or IGF-I (7nM), respectively, when IGF-I is applied 1 hour before the induction of Hebbian LTP. Analyzing the cellular basis of this bidirectional control of synaptic plasticity, we observed that while 10nM IGF-I generates LTP (LTPIGF-I) of the post-synaptic potentials (PSPs) by inducing long-term depression (LTD) of the inhibitory post-synaptic currents (IPSCs), 7nM IGF-I generates LTD of the PSPs (LTDIGF-I) by inducing LTD of the excitatory post-synaptic currents (EPSCs). This bidirectional effect of IGF-I is supported by the observation of IGF-IR immunoreactivity at both excitatory and inhibitory synapses. Therefore, IGF-I controls the induction of Hebbian NMDAR-dependent plasticity depending on its concentration, revealing novel cellular mechanisms of IGF-I on synaptic plasticity and in the learning and memory machinery of the brain.